IDENTIFICATION OF SNP SPESIFIC MARKER FOR CRUSTACEAN HYPERGLYCEMIC HORMONE GENE: A SOMATIC GROWTH-RELATED IN GIANT FRESHWATER PRAWN (Macrobrachium rosenbergii) - Asep Sopian; Alimuddin Alimuddin; Imron Imron; Harry Krettiawan; Fajar Anggraeni; Desy Nurul Astuti (Indonesian Aquaculture Journal, 2017)
High size variation of giant freshwater prawn was found in harvest and resulting in low productivity. Marker assisted selection may be useful to generate broodstock that produces progeny with high growth and homogeneity. This study was conducted to obtain growth related molecular marker in giant freshwater prawn. Genomic DNA was extracted from swimming leg (pleiopods) of 10 giant freshwater prawns fifth Generation for existence of SNP identification, consisted of 5 fast growth (FG) and 5 slow growth (SG).  While for SNP confirmation and resolving power of specific primer studies. The pleiopods sample was taken from six generation of 201 giant freshwater prawns, consisted of 129 fast-growth (FG) with 16.06 ± 2.48 g body weight and 72 slow-growth (SG) with 6.05 ± 0.90 g body weight. Oligonucleotide primers were designed according to Gene Bank database of crustacean hyperglycemic hormone (CHH) gene sequence. The amplified DNA fragment was then sequenced. The results of sequencing showed there was one base different in nucleotides of FG and SG prawns. Six set of primers were designed based on those CH gene sequence. PCR analysis resulted one set of primers which showed a specific amplification product of 280 bp for growth. The result of sequence analysis using the basic local alignment search tools showed that the nucleotide sequence of those PCR products had similarity of 99%-100% with CHH gen of M. rosenbergii. Thus, a candidate of growth related molecular marker have been identified for giant freshwater prawn.